Psychology of religion and spirituality in Jewish contexts: A synthetic review - Stein, Laura B. ca. 20./21. Jh. (Archive for the psychology of religion, 2026)
Jewish spirituality and religion include dynamics that are different from other traditions and have important implications for relational forms of spirituality. Certain approaches to relational Judaism (e.g. Mussar) have offered insights for understanding the folk psychology of relational spirituality in Jewish contexts but have not generated empirical research. Existing research in the psychology of Jewish religion and spirituality draws on several theoretical frameworks and has generated helpful findings. In this synthetic review, we foreground the role of theory in psychological research and offer a brief review of several theoretical frameworks used in research on the psychology of Jewish religion and spirituality (cognitive-behavioral, psychodynamic, cultural psychology of religion, and positive psychology). The relational spirituality model (RSM) is summarized as a conceptual framework that could be useful for future research in this area. We use the RSM as a heuristic organizing framework to review several lines of prior empirical research on the psychology of Jewish religion and spirituality that fit within the RSM domains of spiritual dwelling, seeking, and struggles. The final section outlines future directions in research in this area based on the RSM, with particular attention to dimensions of diversity (e.g. gender, sexual orientation), diverse contexts of Jewish spirituality, Jewish spirituality in relation to both mental health suffering and flourishing, and historical trauma. We also highlight the need for research on Jewish spiritual development in communal settings (e.g. congregations, seminaries) to provide a deeper understanding at both individual and communal levels, and interdisciplinary integration with Jewish theology.